Trust and Security Management Protocol for Delay Tolerant Networks Using Information Centric Network Architecture (ICNA) - Arshiya Shajareen, M; Vasundra, S (International Journal of Computer Sciences and Engineering, 2025)
Disconnected MANETs have been called as challenged networks and Delay-Tolerant Network (DTN). A DTN provides interoperable communications with and among challenged environments. A challenged network is defined as a network that has one or more of the following characteristics: high end-to-end path latency; end-to-end disconnection meaning a path between a node pair may never exist; limited resources or limited life expectancy either due to lack of battery power, such as in sensor networks, or node damage as may occur in battlefield deployments. Such networks may never have an end-to-end path from source to destination at a given time. Security concerns for delay-tolerant networks vary depending on the environment and application, though authentication and privacy are often critical. The proposed model implements trust and security management protocols for delay tolerant and self contained message forwarding applications based on information centric networks architecture. Further, it is aimed to test the dynamic trust management protocol design on other trust based DTN applications for showing better utility of the algorithm.